Morphological Productivity and Lexical Innovation in Swahili: Digital Communication and Language Transformation in Social Media Spaces - Makulilo, Prisca Boniphace (Language, Technology, and Social Media, 2025)
Swahili, as a major lingua franca in East Africa, is undergoing significant transformation through digital communication, particularly on social media platforms. This study explores the morphological and lexical innovations emerging in digital Swahili, with a focus on affixation, compounding, and reduplication. Employing a qualitative approach, the research draws data from 150 social media posts, interviews, and group discussions involving 15 Swahili speakers from urban and rural contexts. The findings reveal increased morphological productivity, with speakers integrating foreign lexical items into Swahili through creative adaptation. Code-mixing and hybrid expressions are also prevalent, reflecting both linguistic innovation and sociocultural identity negotiation. While these developments enhance the expressiveness of Swahili in digital settings, they raise challenges related to language standardization and intergenerational comprehension. This study offers new insights into Swahili’s adaptation to digital environments, highlighting its potential as both a technological and cultural medium. The findings inform ongoing discussions in language policy, digital literacy, and the preservation of African languages in globalized communication.